2020
DOI: 10.1111/1468-5973.12295
|View full text |Cite
|
Sign up to set email alerts
|

Towards Resilient Rotterdam? Key conditions for a networked approach to managing urban infrastructure risks

Abstract: Critical infrastructures are increasingly recognized to be playing important roles in urban resilience theory and practice. However, little is known about which governance challenges result from making them an integral part of urban resilience policies and what role city administrations play or could play in the resulting governance arrangements. We address these shortcomings in the scholarly literature by analysing the case of the Dutch city of Rotterdam, which has positioned itself as a front runner with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…To date, construction in water areas is prohibited in Ukraine, which certainly helps to preserve natural landscaping in these areas. A striking example is a coastal strip in Odesa, which contains many trees and shrubs [47][48][49][50].…”
Section: The Constituent Objects Of the Global Level Of The Urbanized...mentioning
confidence: 99%
“…To date, construction in water areas is prohibited in Ukraine, which certainly helps to preserve natural landscaping in these areas. A striking example is a coastal strip in Odesa, which contains many trees and shrubs [47][48][49][50].…”
Section: The Constituent Objects Of the Global Level Of The Urbanized...mentioning
confidence: 99%
“…Mega-projects are typically criticised in the literature for their lack of transparency and democratic control (Harris 2017), and for technocratic and populist approaches that generate a politics of consensus, obscuring the role of ideology in infrastructure planning and strategy (Jessop 2002;Keil 2002). Most associations between the PPP and infrastructure network theme relate to privatised influence over infrastructure network effectiveness, or potential conditions for effectiveness such as strong institutional arrangements (Bolt 2011;Dolla and Laishram 2020;Huck et al 2021;McLean 2018;Musonda 2018).…”
Section: Infrastructure Governance Ownership Modelsmentioning
confidence: 99%
“…In the organizational resilience (or resilience in organizations) line of research, there is a tendency to address, compound, or associate resilience with other topics. Some articles mapped in the co-citations network go in this direction (e.g., Fiksel et al, 2015;Williams et al, 2017) as well as more recent works from 2020/2021-May (Adekola & Clelland, 2020;Huck et al, 2021;Kaplan, 2020). In this line of research, some avenues for theoretical and empirical studies are also observed.…”
Section: Table 7 Most Cited Papers (In the Collection) On Resilience ...mentioning
confidence: 99%